Preference Signaling and Worker-Firm Matching: Evidence from Interview Auctions - Ron A. Laschever; Russell Weinstein (Institute of Labor Economics (IZA), 2021)
We study whether there are improvements in worker-firm matching when employers and applicants can credibly signal their interest in a match. Using a detailed résumé dataset of more than 400 applicants from one university over five years, we analyze a matching process in which firms fill some of their inter- view slots by invitation and the remainder are filled by an auction. Consistent with the predictions of a signaling model, we find the auction is valuable for less desirable firms trying to hire high desirability applicants. Second, we find evidence that is consistent with the auction benefiting overlooked applicants. Candidates who are less likely to be invited for an interview (e.g., non-U.S. citizens) are hired after having the opportunity to interview through the auction. Among hires, these candidates are more represented among auction winners than invited interviewees, and this difference is more pronounced at more desirable firms. Finally, counterfactual analysis shows the auction increases the number and quality of hires for less desirable firms, and total hires in the market.
Keywords: J20; M51; D83; 330; labor markets; signaling; hiring; interview; matching